CYBERSECURITY RESILIENCE IN THE DIGITAL INDIA FRAMEWORK: CHALLENGES AND STRATEGIES - Kumar, Saurabh; Bansal, Garima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid digitization of India, determined by the Digital India creativity, has transformed the nation's socio-economic landscape by integrating technology into governance, financial systems, and daily life. However, this unprecedented digital transformation brings with it significant cybersecurity challenges. The increasing reliance on digital infrastructure exposes critical sectors to threats such as data breaks, ransomware, and cyber-espionage. This paper examines the core challenges faced in achieving cybersecurity resilience within the Digital India framework, including issues of data protection, infrastructural vulnerabilities, and a lack of cybersecurity awareness among users.